2015
DOI: 10.3390/soc5020277
|View full text |Cite
|
Sign up to set email alerts
|

Leadership and Learning: Conceptualizing Relations between School Administrative Practice and Instructional Practice

Abstract: Abstract:In this paper I argue that one problem we face in understanding relations between school leadership and student learning is that core constructs in our work are often variably and weakly defined. Loose constructs pose problems because they contribute to fuzzy research, especially if constructs such as school leadership, management, or even instruction are weakly (or never explicitly) defined and operationalized. Fuzzy conceptualization makes comparing across studies, essential to the development of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 45 publications
0
44
0
5
Order By: Relevance
“…Spillane (2015) regarded organizational learning as various adjustments for the fundamental belief, attitude & behavior, and structural arrangement in the process to cope with environmental changes in order to enhance the operating effectiveness and the permanent survival and development of enterprises or institutions. Such adjustments were realized through formal and informal interpersonal interaction (Kaiser et al, 2013).…”
Section: Organizational Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Spillane (2015) regarded organizational learning as various adjustments for the fundamental belief, attitude & behavior, and structural arrangement in the process to cope with environmental changes in order to enhance the operating effectiveness and the permanent survival and development of enterprises or institutions. Such adjustments were realized through formal and informal interpersonal interaction (Kaiser et al, 2013).…”
Section: Organizational Learningmentioning
confidence: 99%
“…Taylor (2013) revealed that an enterprise would seek for required intelligence and information from external organizations, such as suppliers, customers, distributors, or government departments, and even search for new clues or concepts from competitors to create new knowledge. Spillane (2015) proposed that an organization, in highly competitive environments, would acquire necessary intelligence and information through customers and competitors to create knowledge. When external environments were stable, old knowledge and experiences in the organizational memory were utilized for creating the knowledge required for the organization (Lubik et al, 2013).…”
Section: Organization Innovationmentioning
confidence: 99%
“…Evidence from different types of educational institutions confirms the idea that some leadership practices are valuable, in almost all contexts (Leithwood, 2011). For Spillane (2017) there is a perspective of DL, which recognizes the existence of several leaders, and as explained by Harris (2012), the activities are widely shared within and between the organization. Primarily, The characteristics of the distribution model focus on interactions, rather than actions, supervisors, and on informal leadership roles.…”
Section: An Approximation To the Concept Of Distributed Leadershipmentioning
confidence: 59%
“…For Elmore (2005 the important thing is instruction, improvement and school performance. To a large extent, Spillane (2017) based the study on distributed cognition to generate the theory of DL. The DL of the school center is one of the most vibrant elements with which schools have in order to be effective and to achieve quality results; school leaders are able to influence and shape the conditions in which they occur (Leithwood et al, 2006).…”
Section: An Approximation To the Concept Of Distributed Leadershipmentioning
confidence: 99%
See 1 more Smart Citation